Nanoemulsion strategies in controlling fungal contamination and toxin production on grain corn using essential oils - Padrilah, Siti Nadzirah; Samsudin, Nik Iskandar Putra; Abd Shukor, Mohd Yunus; Masdor, Noor Azlina (Taylor and Francis, 2024)
Malaysia is currently experiencing a feed shortage, and compounded with the contamination of feed, especially corn, a further shortage of feed is expected in the near future. Nanosciencebased technologies have recently become a hot topic in the agricultural sector as a way to improve the quality of agricultural products. Nanoemulsion is a major thrust in this field because it is easily formulated with a variety of ingredients and equipment. Oil-in-water nanoemulsions, in particular, are being used as delivery methods for a variety of hydrophobic compounds for use in agricultural products, including essential oils. The use of essential oil in the form of nanoemulsions as a fungal inhibitor to reduce fungal growth and fungal toxin production is the way forward for use in corn grain storage. The focus of this review is to compile and analyze the current body of information on the use of nanoemulsion-based delivery systems containing essential oils to control storage grain pathogens in general and corn grain in particular. As the use of essential oil in the form of a nanoemulsion for controlling mycotoxin contamination in corn grain storage is poorly reported, the information from this review will be useful for such work in the future.